Modification of Glassy Carbon Electrodes on Starch-Based for Detection of Chromium Hexavalent - Asnaili Alfi Nurillah; Ani Mulyasuryani; Hermin Sulistyarti (Jurnal Kimia Valensi, 2022)
The purpose of this study was to study the effect of the percentage of the addition of conductivity material in phosphorylation starch to modify GCE (glassy carbon electrode) for detection of Cr(VI). In this study, the technique used is DPV (Differential Pulse Voltammetry). The conductivity material used in this study is activated carbon and Fe3O4 nanoparticles. The method used is an optimization of conductivity material in phosphorylation starch and determination of the performance of the obtained sensor. The optimum percentage of conductivity materials, both activated carbon and Fe3O4 nanoparticles, in the phosphorylation starch matrix is 5%. The form of amorphous activated carbon and the structure trigonal of Fe3O4 nanoparticles affects the current of Cr(VI). The addition of conductive material increases the current of Cr(VI) and shifts the peak potential to the left. The performance of PSC1 sensor is a detection limit of 5,09 ppm and sensitivity of 0,2098 ppm/µA in the linear concentration range of 2,6 – 15,6 ppm. However,  the performance of PSN1 sensor is the detection limit of 3,48 ppm and sensitivity of 0,2120 ppm/µA in the linear concentration range of 2,6 – 18,2 ppm.